Conservative Management of Dushta Vrana (Chronic Ulcer) Through Ayurveda: A Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Non-healing ulcers or Dushtavrana possess a great challenge to the doctors, as it is a very common problem presented by the patients. It is not only that the patient feels the pain and discomfort but the others who look at the patient, they also feel a lot of discomfort. It creates a very embarrassing situation for the patient in his day to day life. After trying for all the therapies eventually patient looks forward to Ayurvedic system of medicine with a very little ray of hope that here his ulcer may be healed. Fortunately only with the help of Ayurvedic medicines and without any sort of surgical intervention the patient get healed. This article presents the conservative management of non-healing ulcers or Dushtavrana which proved to be a miracle for the patients.